Interview with Dr. Fernando Escobar Muñoz: reflections on learning of Pediatric Dentistry in years of pandemic - Pérez-Flores, Antonieta (2021)
Professor Escobar has a recognized career path in international pediatric dentistry, and from that point of view he shows us his Reflections on learning of Pediatric Dentistry in years of pandemic. From his perspective, it is very sobering to take a look at the situation of specialists in Pediatric Dentistry, as a result of this long process of adaptation and learning, which has meant a turning point for professional practice. Most children and adolescents have never experienced a pandemic or even social distancing and strict lockdown, forcing redoubled efforts to avoid the risk of physical and psychological repercussions. The pediatric dentist has the possibility and the competencies to act holistically in front of his patients, take care of children in all the complexity of their biological, psychological and social reality, as the scenario of the pandemic has shown, and promote well-founded policies of public oral health. It is a responsibility to assume and a challenge that must be fully faced, by professionals who are proven suitable, committed and supportive.